ANALYSIS OF INNOVATION STRATEGIES TO INCREASE THE COMPETITIVE ADVANTAGES OF ULOS PRODUCTS IN PEMATANGSIANTAR CITY - Fitria Halim; Sherly Sherly; Ernest Grace; Darwin Lie; Acai Sudirman (JURNAL MANAJEMEN DAN BISNIS, 2021)
One of the production sectors that has become the flagship product of Pematangsiantar City is ulos cloth. Ulos cloth is a typical woven fabric of the Batak community developed for generations in North Sumatra, one of which is the city of Pematangsiantar. This study aims to explore various information related to the number of ulos craftsmen in Pematangsiantar city to facilitate the government in grouping these ulos craftsmen and as a first step to formulate an innovation strategy for the development of creative ulos fabric production to be able to develop superior products armed with knowledge. knowledge, creativity, innovation and being able to create jobs for the community. This type of research is qualitative with a one-shot model, namely an approach model by conducting one-time data collection on an object of research. The research subjects taken in this study were ulos craftsmen spread across eight sub-districts of Pematangsiantar City. The analysis was carried out in eight sub-districts in Pematangsiantar City. Data collection techniques using observation, interviews and questionnaires, field notes and documentation.The results of the study concluded that the innovation strategy applied by the ulos fabric craftsmen was not optimal, this was due to the limited capacity and opportunity to innovate, the ulos craftsmen experienced problems in making product innovations related to technological limitations caused by limited investment capital to buy new machines or equipment. to improve production processes and limited human resources who can operate new machines or make innovations that take advantage of technological developments.